A methodological approach to dematerialization of business processes using open-source technology - Ávila, Liliana (2021)
Projects of dematerialization of business processes allow organizations to modernize their administrative activities through the rationalization and optimization of information flows and elimination of documents circulating in paper format. In this article is proposed a methodology for the implementation of projects of dematerialization of business processes in public and private organizations constituted by four stages: preliminary studies and requirements elicitation, modelling, construction and transition. It is also described a pilot-experience in a public entity using an open source software (Bonita Open Solution) in order to validate the proposed methodology and confirm open-source technologies as a good option to implement this type of projects in a low-cost approach. Furthermore, throughout the paper, some guidelines are provided based on critical success factors and tools to support development stages.